Anxiety and social skills indicators of college students during COVID-19 pandemic (Research, Society and Development, 2022)
Studies from different countries verified the relationship between deterioration of quality of mental health and academic engagement decrease of college students during pandemic period of COVID-19. This study aim to describe indicators of academic engagement, anxiety, academic anxiety, and social skills (SK) of college students during COVID-19 context. Participants were 88 college students of different semesters of a undergaduate course of Psychology from the interior of State of São Paulo. Data were collected in 2020 by an online questionnaire. Main results indicated: a) participants of the 7th semester achieved greater mean of academic engagement, academic anxiety and SK; and participants of the 5th semester achieved the lower mean oh the same indicators; b) statistics correlations between SK categories and academic engagement; SK categories and academic anxiety categories. Final considerations suggest the results corroborate the literature on damage to mental health in college students as a result of coping with the pandemic.